Explorative Study on the Impact of Pandemy on the Tourism Services Industry in West Java - Kurniawan Kurniawan; Koesmawan Koesmawan (International Journal of Supply Chain Management, 2021)
The Covid-19 pandemic affects almost all sectors of life. The Covid-19 virus attacks the world's economies, including Indonesia. The tourism sector has even felt its impact since the beginning of 2020. Fear of traveling, both domestic and foreign travel, as well as policies and instructions to stay at home to prevent transmission of the virus, create a domino effect on tourism supporting sectors, such as hotels, restaurants and retail business. In West Java alone, according to the Head of West Java Tourism and Culture Office, Dedi Taufik, as of April 16, 2020, there were 2768 tourism businesses consisting of tourist destinations, hotels, and creative economy activity in closed areas. This resulted in the loss of livelihoods, tens of thousands of tourism workers. In West Java, 33,084 tourism workers were unemployed. Research was carried out in several locations in West Java during the pandemic. The method used in this research is descriptive qualitative research, that describes the object of research based on visible facts or as they are. Respondents were selected purposively by selecting 8 respondents according to research objectives including tourism industries agents (restaurants, spas, hotels and MICE), tourism researchers and policy makers (local government).